(untitled) (Revista Brasileira de Contabilidade e Gestão, 2025)
This study analyses the contribution of electronic money to promoting financial inclusion and stimulating economic growth in Mozambique, consideringthe structural limitations of the traditional banking system. Method(s): A quantitative approach was used, based on econometricmodels of panel data with fixed and random effects, validated by the Hausman and Breusch-Pagan tests. The analysis focused on indicators of Gross Domestic Product (GDP) and the Financial Inclusion Index (FII). Empirical evidence indicates that electronic money has a positive and statistically significant impact on expanding access to financial services. A positive association with GDP was also found, signaling its role as a driver of economic growth. Based on the data obtained, our results reinforce the potential of electronic money as a mechanism for financial inclusion and economic development, while pointing to the urgency of specific public policies that promote digital access.